Effect of foundation flexibility of concrete moment resistant frame on drift - Iman Hakamian (مهندسی و مدیریت ساخت, 2024)
The effects of the foundation flexibility on Structural drift has been considered in concrete moment resisting frames in this paper. The foundation flexibility influences the total base shear reaction and its distribution directly. To analysis the base shear measurement, the near-field earthquakes were used as lateral external forces. In this study three concrete moment resisting frames 7, 10 and 15 story with 22.2m, 31.8m and 41.8m height were investigate that their bays are 5.5m in all of cases. To model the flexible foundation, Beam Nonlinear Winkler Foundation (BNWF) method was used. In this method, linear inelastic springs were used in vertical and horizontal directions. After base shear measurement, the structural drifts of concrete moment resisting frames have been compared in the case of flexible and fix-based foundation. The distribution of shear base pattern and drift values in fix-based foundation are totally different from flexible-based. The difference is observed in all height level structures.